EFFECTIVENESS OF SOCIOSCIENTIFIC ISSUE-ORIENTED PBL MODEL TO IMPROVE REPRESENTATION ABILITY - Masruroh, Latifa Dwiani; Muna, Izza Aliyatul (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
Along with the development of dynamics in science education, the development of education and technology. Teachers are expected to apply a model of learning that can facilitate students so that they have the ability to think creatively, innovatively and critically. The results of a preliminary study conducted at MTs Ma'arif Al-Mukarom showed that representation skills were still relatively low with a learning model that was less varied. This study aims to determine 1.) the activity of students towards learning with a Socioscientific issues-oriented PBL learning model to improve representation ability, and 2.) the effectiveness of the Socioscientific issues-oriented PBL learning model to improve representation skills. This type of research is quantitative, namely experimental research. The population in this study were students in grade VIII with the research sample of class VIII-A as the experimental class and VIII-B as the control class at MTs Ma'arif Al-Mukarom Ponorogo. The data collection techniques in this study were observation of learning implementation, observation of students' activities, and pretest and posttest of representation skills. The results showed that the results of the student activity sheet showed that the percentage of activities in learning obtained an average of 91.67% which was included in the first criterion was very good. In the effectiveness test, the results of the ancova test showed that the class that used the socioscientific issues-oriented PBL model had high representation skills.